Performance of Local Employment Systems - Tomas Hanell; Lars Olof Persson (European Regional Science Association (ERSA), 2003)
At the national level the employment system consists of the set of institutions, and policies affecting institutions, which together moderate the level of production, employment and unemployment in the country (Schmid, G. & Gazier, B. eds. 2002. The Dynamics of Full Employment. Edward Elgar). These institutions include employment legislation, taxation policy and the education and training systems. However, the dynamics and the complexity of the national labour markets could only be understood by analysing the systemic character of employment at the regional and local levels. The regional and local social systems function as filters or restrictions, resulting in differing performance of local labour markets. The interaction between the labour market and the local educational and private household systems – including its various preferences and life-style options - is reflected in, and allowing for, differing rates of transition between alternative statuses at the labour market. This seems particularly valid in a country like Sweden, where there is a wide variation of functional labour markets in terms of size, differentiation, settlement and demographic structure. Also, the recent cut backs and weakened intervention of the welfare state in general combined with an increasingly dominating role of the public sector as an employer in regions with an ageing population suggest an emerging divergence in the performance of local labour markets. In this paper, we suggest that the performance of local employment systems should be evaluated in terms of the rate of activation of local pools of labour force and of immigration. Well functioning employment systems should facilitate voluntary and temporary entries to and exits from employment to other statuses, e g to and from education and training. Rapid activation should be facilitated of the local pools of unemployed and other non-employed including persons on long-term sick leave. Preliminary results from empirical analysis based on longitudinal data reveal that there is a wide variation in performance of Swedish local labour markets in these terms and that there are no signs of convergence over the period 1990-99. The results suggest that national policies to affect institutions within the employment system has to be synchronized with and supported by regionally differentiated measures to improve the local social systems, in particular within the local education system, to improve working conditions in certain sectors and also to promote local mobility between economic and non-economic sectors.
Keywords: 330